Implementasi Ranham Generasi Ketiga tentang Pencemaran Udara dan Air Akibat Limbah Industri di Provinsi Jawa Timur - Firdaus, Firdaus (Jurnal HAM, 2014)
National action plans on human rights (ranham) the third generation is an attempt is conceived of as the guidelines of reverence, protection, promotion and fulfilment of human rights and human rights to the state responsibilities and obligations for citizens. But in the implementation of not in accordance with government policy, the focus of local governments must consider, the potential, and the problems not yet fulfill the good and healthy environment for the community. The condition of the environmental quality that is less good on water and air pollution caused by industrial waste.This writing ranham trying to unravel the readiness of the implementation of the committee, and to know local government policy in order to ranham pro environment. A method of the research uses a method of qualitative berciri descriptive analytical, with data collection techniques primary and secondary sources of accurate data, the inventory of the legislation relating to data.